MODEL TRANSPORT DEMAND BANDAR UDARA SYAMSUDIN NOOR BANJARMASIN - Ginanjar Priadikusumah (Jurnal Teknologi Berkelanjutan, 2019)
Syamsudin Noor Airport, which function has been changed to the Central Dissemination Airport since 2007, will definitely experience an increase in aircraft movements, passenger movements and goods. To provide infrastructure and facilities that meet these needs, it is necessary to make predictions about the needs that will occur. The need of passengers is a function of the free variable, where in general candidates for the free variable are characteristics of population activities that are reflected in the form of land use and demographic and socio-economic characteristics of the population. By using a basic service area around the airport and using demographic and socio-economic factors in the service area, a trip generation model from Syamsudin Noor airport was created. The modeling formula based on the best formulation for passenger departures is: Y = 28626,596 + 5,861.X1 + 215,232.X2 with a value of R2 = 0.890, the variables that determine Foreign Tourists (X1) and Industrial Workers (X2). Formulation for passenger arrivals: Y = 29371,093 + 6,346.X1 + 201,443.X2 with a value of R2 = 0,891, the variable that determines Foreign Tourists (X1) and Industrial Workers (X2). The transport demand model obtained is used as a basis for predicting the number of domestic air passengers at Banjarmasin Syamsudin Noor Airport.